The Influence of Antenatal Education on Mothers' Readiness to Face Childbirth - Fitria, Henny; Yusriana, Novia; Pratama, Syahran (International Journal on ObGyn and Health Sciences, 2025)
This research investigates the influence of antenatal education on mothers’ readiness to face childbirth, focusing on its impact on physical, emotional, and psychological preparedness. The study explores how structured antenatal education programs can improve maternal knowledge, reduce anxiety, increase self-confidence, and contribute to a more positive birth experience. Data were collected through surveys and interviews with expectant mothers who participated in antenatal education classes, and the findings were analyzed to assess the effects of education on maternal preparedness for labor and delivery. The results indicate that antenatal education significantly enhances mothers' readiness by providing them with essential information about the childbirth process, coping strategies, and self-care techniques. Furthermore, participants in the education program reported lower levels of anxiety and greater satisfaction with their birth experience. The study also highlights the challenges related to access to antenatal education, particularly in rural and underserved areas, and emphasizes the need for culturally sensitive and accessible programs. These findings suggest that improving access to antenatal education can empower mothers, reduce maternal and neonatal complications, and improve overall maternal health outcomes. The research provides valuable insights for healthcare providers and policymakers, offering recommendations for enhancing antenatal education programs to better support expectant mothers.